Kepemimpinan Pesantren untuk Menyiapkan Pemimpin Bangsa Bermoral dalam Menyongsong Bonus Demografi - Fatiya Nur Azizah; Dzakkiyah, Siti (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2021)
The purpose of education is directed to be able to produce professional academic graduates for the development of knowledge and improvement of people's living standards. The public's view of the function of Islamic boarding school education is also called the second educational institution, but graduate from Islamic boarding schools and their benefits in community leadership prove that Islamic boarding school education also contributes a lot to national development, Islamic boarding school education as an educational institution to produce good human resources in the face of the demographic bonus to In the future, the demographic bonus is an opportunity for Indonesia but if it is not prepared properly it can become a challenge for Indonesia. If a leader and all elements of the government are able to prepare a professional workforce and are able to create employment opportunities to absorb the entire available workforce. The biggest challenge in preparing the demographic bonus is how the leaders and all staff are able to manage the large population of productive age to be productive from various fields. The purpose of this study is an attempt to explain the concept of the implications of pesantren leadership in preparing moral nation leaders, especially those from pesantren graduates who will be capable in facing the demographic bonus era in the future by having expertise in the field of religion. In this study, using a literature study method with a qualitative approach.